A facile synthesis of two new IR optical perovskites based on 1, 4-diazabicyclo[2, 2, 2]octane with a high laser damage threshold. Issue 41 (3rd October 2018) - Song, Jun-Ling; Chen, Wen-Jun; Chu, Kai-Bin; Zhou, Yu-Hua
Abstract : Two new IR optical perovskites based on 1, 4-diazabicyclo[2, 2, 2]octane, namely, (H2 dabco)(PbCl3 )2 (1 ) and (H2 dabco)(H2 PbBr6 )·H2 O (2 ), were discovered and they both crystallize in the noncentrosymmetric space group P 43 21 2 and P 63 mc, respectively, displaying broad transparent range with high transmission. Abstract : The main commercial infrared nonlinear optical (IR NLO) crystals, typically, AgGaS2, have some inherent disadvantages, for example, low laser damage threshold (LDT) or relatively poor stability, which limit their wide application. Here, we discover two new IR optical perovskites based on 1, 4-diazabicyclo[2, 2, 2]octane, namely, (H2 dabco)(PbCl3 )2 (1 ) and (H2 dabco)(H2 PbBr6 )·H2 O (2 ).1 and2 crystallize in the noncentrosymmetric space groups P 43 21 2 and P 63 mc, respectively, displaying a broad transparent range with high transmission. Particularly, compound2 exhibits a moderate SHG response of 1.8 times that of KH2 PO4 (KDP) at 1064 nm with a high laser-induced damage threshold of 328.8 MW cm −2, indicating that it is a new promising NLO material.